John and 2 friends are going out for pizza for lunch. They split one pizza and 3 large drinks. The pizza cost $14.00. After using a $7.00 gift certificate, they spend a total of $12.10. Write an equation to model this situation, and find the cost of one large drink.A. 3d + $14.00 – $7.00 = $12.10; $1.90

B. 3d – $14.00 + $7.00 = $12.10; $9.55

C. 3d + $14.00 – $7.00 = $12.10; $1.70

D. 2d + $14.00 – $7.00 = $12.10; $2.55

Answers

Answer 1
Answer:

Answer:

The equation to model this situation is  3d + $14.00 – $7.00 = $12.10 and the cost of one large drink is $1.7 .

Option (C) is correct .

Step-by-step explanation:

As given

John and 2 friends are going out for pizza for lunch.

They split one pizza and 3 large drinks. The pizza cost $14.00. After using a $7.00 gift certificate, they spend a total of $12.10.

let us assume that the numbers of large drinks are represented by d .

Than the equation becomes

Total money spend = Number of drinks × d + Pizza cost  - Gift certificate amount .

Putting all the values in the above

12.10 = 3d + 14.00 - 7.00

Simplify the aboves

12.10 = 3d + 14 - 7

12.10 = 3d + 7

12.10 - 7 = 3d

5.1 = 3d

d = (5.1)/(3)

d = $ 1.7

Therefore the equation to model this situation is  3d + $14.00 – $7.00 = $12.10 and the cost of one large drink is $1.7 .

Option (C) is correct .

Answer 2
Answer: Its no D because you need to divide by 3 not 2. Your answer should be C.

Related Questions

How to find the value of this expression
In a triangle the base is 4 inches and the height is 6 inches. Find the area.12 in.²12√3 in.²24 in.²
Over two summers, Ray saved $900 and $500. The polynomial 900x2 + 500x represents his savings at the beginning of the third year, where x is the growth factor. (The interest rate r is x - 1.) What is the interest rate he needs to start the third year with $1600 in savings? A. 0.1% B. 1.1% C. 8.4% D. 264%
7a-3=3-2aI don't know how to solve this question
Find (fog)(x). f(x) = 2x g(x) = x + 6write your answer as a polynomial in simplest form. (f•g)(x)=​

Two functions, y = |x - 3| and 3x + 3y = 27, are graphed on thesame set of axes. Which statement is true about the solution to the
system of equations?
(1) (3,0) is the solution to the system because it satisfies the equation
y = |x - 3|.
(2) (9,0) is the solution to the system because it satisfies the equation
3x + 3y = 27.
(3) (6,3) is the solution to the system because it satisfies both equations.
(4) (3,0), (9,0), and (6,3) are the solutions to the system of equations
because they all satisfy at least one of the equations.

Answers

                        y = |x - 3|
              3x + 3y = 27
       3x + 3|x - 3| = 27
       3x + 3|x - 3| = ±27
       3x + 3|x - 3| = 27        or          3x + 3|x - 3| = -27
       3x + 3(x - 3) = 27        or         3x + 3(x - 3) = -27
   3x + 3(x) - 3(3) = 27     or       3x + 3(x) - 3(3) = -27
          3x + 3x - 9 = 27        or           3x + 3x - 9 = -27
                  6x - 9 = 27           or                6x - 9 = -27
                      + 9   + 9                                  + 9   + 9
                       6x = 36               or                 6x = -18
                        6      6                                     6       6
                         x = 6                  or                  x = -3
                         y = |x - 3|           or                  y = |x - 3|
                         y = |6 - 3|           or                  y = |-3 - 3|
                         y = |3|                or                  y = |-6|
                         y = 3                  or                  y = 6
                   (x, y) = (6, 3)           or            (x, y) = (-3, 6)

The two systems of equations of the graph is only equal to (6, 3). It is not equal to (-3, 6) because one of the systems of equations - y = |x - 3| - only has one solution to the function. So the answer to the problem is 3 - (6, 3) is the solution to the system because it satisfies both equations.

How do I solve for x? log (x-2) = -1 + log (x+1)

Answers

For this question you can say:
log(x-2) - log(x+1) = -1 
and you should know that log(x-2) minus log(x+1) is equal to:
log((x-2)/(x+1)) 
so now you have:
log((x-2)/(x+1)) = -1 
now you can say:
(x-2)/(x+1) = 10^ -1 or (x-2)/(x+1) = 1/10 
now you can say:
10(x-2) = x+1 
10x -20 = x +1 
10x - x = 20+1 
9x = 21 
x = 21/9 
x = 7/3 :)))
I hope this is helpful
have a nice day

What is 120 US fl oz in US liquid quarts

Answers

3.75 quarts

Brainly plz and thank you

Graph ​ y=−4/7x+1 ​. Please help.

Answers

Answer:

The required graph is shown below.

Step-by-step explanation:

Consider the provided function.

y=-(4)/(7)x+1

The above function is a linear function.

We can draw the graph of the function with the help of 2 points.

Substitute x = 0 in the above function.

y=-(4)/(7)(0)+1

y=1

Substitute y = 0 in the above function.

0=-(4)/(7)x+1

(4)/(7)x=1

x=(7)/(4)

Now plot the points.

Draw a straight line passing through (0,1) and (7/4,0)

The required graph is shown below.

Go to a website called desmos graphing calculator and it will help you out but I put a image of the graphed equation as well.

Which is greater 8 quarts or 16 pints?

Answers

They're equal because 1 quart = 2 pints.

F(x)= -2x^2 +8x -12 in vertex form

Answers

            f(x) = -2x² + 8x - 12
               y = -2x² + 8x - 12
          + 12                  + 12
       y + 12 = -2x² + 8x
y + 12 - 8 = -2x² + 8x - 8
        y - 4 = -2(x²) - 2(-4x) - 2(4)
        y - 4 = -2(x² - 4x + 4)
        y - 4 = -2(x² - 2x - 2x + 4)
        y - 4 = -2[x(x) - x(2) - 2(x) - 2(-2)]
        y - 4 = -2[x(x - 2) - 2(x - 2)]
        y - 4 = -2(x - 2)(x - 2)
        y - 4 = -2(x - 2)²
          + 4         + 4
             y = -2(x - 2)² + 4